2019
DOI: 10.1186/s13229-019-0303-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ca2+ signaling in NRXN1α+/− neurons derived from ASD induced pluripotent stem cells

Abstract: BackgroundAutism spectrum disorder (ASD) is a neurodevelopmental disorder with a high co-morbidity of epilepsy and associated with hundreds of rare risk factors. NRXN1 deletion is among the commonest rare genetic factors shared by ASD, schizophrenia, intellectual disability, epilepsy, and developmental delay. However, how NRXN1 deletions lead to different clinical symptoms is unknown. Patient-derived cells are essential to investigate the functional consequences of NRXN1 lesions to human neurons in different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 95 publications
(105 reference statements)
2
35
0
Order By: Relevance
“…Several genetic forms of ASD show a decrease in the number of neurons and synapses, including Timothy syndrome-in which there was a decrease in the fraction of neurons expressing lower layer markers [142] and 22q11.2 deletion, which showed a reduced number of neurons accompanied by an increase in the number of astrocytes [124]. Three studies on NRXN1 mutations also found evidence for a decrease in neuronal maturation [134,135,137], a finding which was not replicated in a different study [136]. Similar results (downregulation of neuronal processes) were indirectly observed using transcriptomic analysis from neurons in which CHD8 was either knocked down [132] or heterozygously deleted [131].…”
Section: Neuronal Differentiation and Morphologymentioning
confidence: 98%
See 1 more Smart Citation
“…Several genetic forms of ASD show a decrease in the number of neurons and synapses, including Timothy syndrome-in which there was a decrease in the fraction of neurons expressing lower layer markers [142] and 22q11.2 deletion, which showed a reduced number of neurons accompanied by an increase in the number of astrocytes [124]. Three studies on NRXN1 mutations also found evidence for a decrease in neuronal maturation [134,135,137], a finding which was not replicated in a different study [136]. Similar results (downregulation of neuronal processes) were indirectly observed using transcriptomic analysis from neurons in which CHD8 was either knocked down [132] or heterozygously deleted [131].…”
Section: Neuronal Differentiation and Morphologymentioning
confidence: 98%
“…Two kinds of genetic modeling have been performed using cells either from individuals whose genetic contributions are unknown or undefined, so called idiopathic [59,60,[112][113][114][115][116][117][118][119][120], or from individuals harboring major effect mutations that are presumed causal or which have been engineered to carry these mutations. These mutations include ASD-associated CNVs such as 15q11q13 deletion (Angelman syndrome) [121] and duplication (Dup15q syndrome) [122], 22q11.2 deletion (DiGeorge syndrome) [123,124], 16p11.2 deletion and duplication [125], and 15q13.3 deletion [126], as well as single-gene mutations including SHANK3 [127][128][129][130], CHD8 [131,132], NRXN1 [133][134][135][136][137], NLGN4 [138], EHMT1 (Kleefstra syndrome) [139], PTCHD1-AS [140], UBE3A (Angelman's syndrome) [141], and CACNA1C (Timothy syndrome) [142] (summarized in Table 1). In this review, we will not discuss fragile X syndrome, Rett's syndrome, and tuberous sclerosis-related autism as they have all been extensively reviewed previously [148][149][150][151][152][153][154].…”
Section: Main Findings From Stem Cell Models Of Asd To Datementioning
confidence: 99%
“…As for the identified hub miRNA sponges, functional enrichment analysis results indicate that they are significantly enriched in SMAD binding (GO: 0046332). A previous study ( Avazzadeh et al, 2019 ) has demonstrated that SMAD binding is closely related to ASD. Altogether, the above functional enrichment analysis results imply that the identified hub genes are closely associated with the occurrence and development of ASD.…”
Section: Resultsmentioning
confidence: 96%
“…Different results have been communicated regarding the functional consequences of mutations in NRXN1 , which encodes for a presynaptic membrane cell adhesion protein. Avazzadeh et al demonstrated that glutamatergic cortical neurons derived from NRXN1α +/− iPSC lines exhibit increased frequency, duration and amplitude of calcium transients in comparison to control neurons derived from healthy donors [ 78 ]. On the other hand, neurons differentiated from patient iPSCs with biallelic NRXN1α deletion displayed a decreased amplitude and slower rise time of depolarization-evoked calcium transients, as well as a reduction in action potential amplitude [ 79 ].…”
Section: Asd-related Phenotypes In 2d Modelsmentioning
confidence: 99%